EFFECTIVENESS OF PEER EDUCATION IN DECREASING ADOLESCENT PREGNANCY: A LITERATURE REVIEW - Anak Agung Istri Dalem Cinthya Riris; Ni Kadek Diah Purnamayanti (JURNAL KESEHATAN REPRODUKSI, 2021)
Abstract Background: Currently, the number of adolescents who have sexual intercourse is increasing and those make a higher risk of medical, psychological, and social implications. This behaviour is obviously leading to an increase the number of adolescence pregnancy. Sex education and counselling in many countries is delivered by health care professionals. In Indonesia, there are some sex education programs delivered by peer educators but their success in reducing adolescence pregnancy is unknown. Objective: The aim of this study was to analyze the effectiveness of a peer reproductive health education program in decreasing unplanned pregnancy in adolescents. Method: This integrative literature review was based on 3 databases which included Google Scholar, Pubmed and SAGE Journal. The inclusion criteria were articles published within the 2012–2018-year range, written in English, and the entire article was available and accessible. Only original articles with experimental design will be included. The quality of the selected articles was defined by using the Olsen-Baisch Scoring critical appraisal tool for integrative review. Result: Peer education builds social support and sense of belonging. The content is not only about unplanned pregnancy but also STI and HIV; responsible decision making; and body image identification. Peer educator can be the role model and have greater opportunities to counter the risk of adolescent pregnancy. Conclusion: Preventing adolescent pregnancy can save the next generation and improve adolescent health. Peer educator as part of health provider connect adolescents with their reproductive health needs. This approach would be beneficial strategy consider by health provider to protect adolescents. Keywords: adolescent, peer educator, pregnancy, sex education